RISK FACTORS OF PERINATAL DEPRESSION IN WOMEN: AN UPDATED SYSTEMATIC REVIEW - Investari Nugraheni, Artha; Amelia Rahmah, Dini; Agus Prastyo, Wahyu; Azhari, Ririn; Merisa L, Bella; Ananda, Astrid; Syarfina, Afdila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Perinatal depression (PND) can result in adverse outcomes for both mother and child, including poorer pregnancy outcomes and long-term emotional, social, and cognitive difficulties in children. Furthermore, it correlates with high morbidity and mortality rates, posing significant burdens on affected individuals, families, and society. The objective of this study is to conduct an extensive systematic review evaluating the risk factors of perinatal depression in women based on literature published within the last five years. Methods: The systematic review followed PRISMA 2020 standards and examined full-text English literature published between 2019 and 2024. This review excluded editorials, review papers from the same journal, and submissions without a DOI. Literature was sourced from online platforms such as PubMed, SagePub, and SpringerLink. Result: A total of 1,161 articles were retrieved from online databases (PubMed, SagePub, and SpringerLink). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Perinatal depression (PND) affects numerous women during and after childbirth, influenced by socioeconomic, psychosocial, and environmental factors like poverty, social support, pregnancy loss, and urban living. Early detection and comprehensive interventions are crucial to support at-risk mothers, promoting better mental health outcomes for both them and their families.